"The Future of Korean Buddhism Lies in My Hands": Takeda Hanshi as a Sōtō Missionary - Kim, Hwansoo Ilmee (Japanese journal of religious studies, 2010)
Was the work of Japanese Buddhist missionaries "evil," as many historians have indicated? To problematize this view, this article revisits the most vilified of Japanese Buddhist missionaries of the pre-colonial and colonial period (1877-1945). Takeda Hanshi (1863-1911) was both a staunch imperialist and a Sōtō Buddhist priest. His infamy in politics derives from his participation in the assassination of the queen of Korea and enabling Japan's annexation of Korea. For Buddhists, he is the mastermind behind the Sōtō sect's attempt to control Korean Buddhism through an alliance with its first modern institution, the Wŏnjong. Scholars have focused on these three events, thus reinforcing the view that Takeda was the epitome of Japanese imperial aggression. However, a close examination of Takeda's writings from 1907 to 1911 sheds new light on his missionary work. I argue that despite his imperial ideology, Takeda made strenuous efforts, until 1910, to promote the Wŏnjong and defend its autonomy. Based on overlooked primary sources, this article presents a case study that furthers recent scholarly calls to move beyond the imperialist/victim or hero/traitor framing of colonial Korean Buddhist history.